Claws for suspicion - Blake, Deborah (Writer of paranormal) (A Catskills Pet Rescue mystery, 2022)
"Kari Stuart is finally starting to relax into her role as the new owner of the Serenity Sanctuary and is looking forward to the various fun autumn activities in the beautiful Catskills town of Lakeview, like the annual Oktoberfest celebration. It's time for friends and quality bonding with handsome vet Angus McCoy. Until the unexpected arrival of her unpleasant ex-husband, Charlie Smith. He comes bearing a shocking revelation--the paperwork on their divorce never went through, and they are still married. Worse yet, he thinks this entitles him to half of her lottery winnings--although he'll happily take partial ownership of the sanctuary instead. Kari isn't sure if he's telling the truth, or if it's just another one of Charlie's lies. But things go from bad to worse when an unexpected death makes Kari the main suspect in a murder investigation. Will she and Queenie be able to find the real killer and keep the home they've built at the sanctuary safe, or is their string of luck finally tapped out?"--Back cover.